2004
DOI: 10.1007/s00726-003-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-translational modifications of alpha A-crystallin from normal and hereditary cataract rats

Abstract: In order to investigate the relationship between lens opacities and the various modifications of lens proteins, we analyzed and compared the properties of lens proteins of 85-day old normal Wistar rats and the hereditary cataract model, ICR/f rats. The present study identified many differences between normal and mutant lens proteins. In the ICR/f mutant rats, the relative amounts of gamma-crystallin decreased and high molecular weight (HMW) protein increased. Racemization and isomerization of Asp-151 of alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Another reason for this was the possibility that the accelerated aspartic acid racemization rate originated from cataracts in lens of old mammals such as human [23] and rat [24]. The amount of changes of Asp D/L in lens of younger animals was higher than older animals, because the Asp D/L exponential decays in lens of mammals, suggesting that k Asp is more precisely estimated for young animals.…”
Section: Standard Error Of Age Estimated By Aarmentioning
confidence: 99%
“…Another reason for this was the possibility that the accelerated aspartic acid racemization rate originated from cataracts in lens of old mammals such as human [23] and rat [24]. The amount of changes of Asp D/L in lens of younger animals was higher than older animals, because the Asp D/L exponential decays in lens of mammals, suggesting that k Asp is more precisely estimated for young animals.…”
Section: Standard Error Of Age Estimated By Aarmentioning
confidence: 99%
“…However, to date, the impact of these modifications on the chaperone ability of sHsps to prevent amyloid fibril formation has not been investigated. This area of study is significant since these post-translational modifications occur to a significant extent to the crystallin proteins in the eye lens [12, [127][128][129][130][131][132][133]. There is increasing evidence that cataract may be an amyloid fibril based disease (see below) and, as such, the impact of such modifications on the chaperone ability of α-crystallin to prevent this process is highly relevant.…”
Section: The Effect Of Post-translational Modifications On the Chapermentioning
confidence: 99%
“…It has also been shown that methionines of αA- and αB-crystallins are oxidized in clear middle-aged (45–65) human lenses [2021]. Importantly, αA-crystallin is found to be oxidized to methionine sulfoxide in rat hereditary cataracts [22] and interestingly, substitution of methionine 68 in αB-crystallin with a less hydrophobic residue (Thr) leads to loss of chaperone activity [23]. These data provide evidence that methionine oxidation plays a key role in cataract formation through loss of α-crystallin chaperone function.…”
Section: Introductionmentioning
confidence: 99%